Analisis Environmental Criticality Index (ECI) di Kawasan Kota Pontianak dengan Pendekatan Google Earth Engine Mengunakan Citra Multi-Temporal Landsat 9 OLI-2 Calibrated TOA - Rangga, Boy; Palureng, Rurika Widya Ningrum; Andini, Febby Ekamukti (Universitas Tanjungpura, 2025)
Pontianak City, a trade and services center in West Kalimantan, faces environmental challenges due to rapid urbanization. In particular, the land use transition from green to building leads to impervious surface expansion with less vegetation and increasing heat on the land surface. In this work, changes contributing to environmental disruptions were thoroughly investigated by Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), and Normalized Difference Water Index (NDWI). The indicators were collected for Environmental Critically Index (ECI) analysis using Google Earth Engine with Landsat 9 OLI-2 TOA imagery. About 91.8% of the total area, especially in densely populated areas, is within a critical level of environmental vulnerability, with 50.63% moderately vulnerable and 41.17% high vulnerability. Urban Heat Island (UHI), flooding, and poor air quality are potential consequences of this case if not properly solved. This work suggests several mitigation efforts, including Green Infrastructure Building implementation, spatial planning regulations oriented with environmental carrying capacity, and a real-time monitoring system that supports the adaptive cities to the ECI index. Thus, this research is on a scientific basis in designing sustainable development policies in tropical regions that are often environmentally affected by urban sprawl.